A Literature Review on the Effect of Tax Planning on Firm Value - Sakinah, Chyntia; Mahmudah, Siti; Wahono, Puji (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the impact of tax planning on firm value through a comprehensive literature review. Using a qualitative approach, this research collects, analyzes, and synthesizes secondary data from various credible sources, including academic journals, theses, textbooks, and Indonesian tax regulations. The findings reveal that effective tax planning can significantly enhance firm value by increasing after-tax profits, improving financial efficiency, and strengthening investor confidence. However, the impact is not uniform across all companies. Several moderating factors influence the relationship between tax planning and firm value, such as firm size, ownership structure, tax regulations, leverage, and corporate governance. While some studies report a positive and significant correlation, others show insignificant or context-dependent effects. This indicates that the effectiveness of tax planning strategies is shaped by both internal and external factors. The study provides practical implications for corporate management, investors, and policymakers in designing balanced and transparent tax strategies that align with regulatory compliance and long-term value creation.